The Relationship between Daoist Rituals and Theatrical Performance: The Case of Xianggong Tapeng in Puxian Theater - Zhang, Lijuan (Religions, 2014)
Daoism is a traditional Chinese religion. Daoism has had a deep and pervasive impact on the lives of China’s peoples. Chinese theatrical performances were often integrated with religious activities, thereby gradually giving rise to many forms of popular drama that are deeply inflected with religious overtones. Xianggong Tapeng (相公踏棚, Xianggong stamps the shed) is one component of Puxian opera’s rites for stage cleaning that is closely linked with Daoist thought. First, Xianggong is both a theatrical spirit within Puxian opera and a member of the Daoist pantheon. Second, the lyric “luo li lian” featured in Xianggong Tapeng bears a remarkable resemblance to the two Daoist spells Yuanshuai Zhou (元帥咒, Incantation of Yuanshuai) and Xiangmo Zhou (降魔咒, Incantation for Subduing Demons). This is due to the fact that traditional Daoist verse often features phrases such as “luo li lian”. Moreover, the stage cleaning rites that are characteristic of Puxian opera share many similarities with Daoist altar purification rites. A detailed investigation and comparison reveal that Xianggong Tapeng is an adaptation of the Daoist altar purification rite to the needs of popular custom and theatrical performance.